Porcelainized fireproof low-smoke halogen-free polyolefin cable material for new energy automobile and preparation method thereof

The porcelain-resistant, low-smoke, halogen-free polyolefin cable material for new energy vehicles prepared through specific ratios solves the problem of the combustion and spread of new energy vehicle cables in fires, achieves excellent flame retardant and fire-resistant performance, protects power supply safety and has multiple functions.

CN119708686APending Publication Date: 2025-03-28YANGZHOU HAONIANHUA POLYMER MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078376.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

New energy vehicle cables are prone to burn instantly during fires, resulting in short circuits, power outages and fires, seriously endangering the safety of life and property. Existing flame retardants can only delay combustion time and affect material performance.

Method used

A new energy vehicle-friendly porcelain-resistant fire-resistant low-smoke halogen-free polyolefin cable material is used to prepare cable materials with excellent flame retardant and fire-resistant properties through specific ratio raw materials (ethylene ethyl acetate, polyethylene, polyethylene wax, maleic anhydride grafted polyethylene, porcelain powder, ammonium phosphate, magnesium hydroxide and antioxidants).

Benefits of technology

The cable material maintains shape and strength in the fire, and will not spread the fire. It has excellent fireproof functions, protecting the power supply safety of the intelligent central control system of new energy vehicles, and has multiple functions of heat insulation, smoke suppression, halogen-free and fire-proof.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a porcelainized fireproof low-smoke halogen-free polyolefin cable material for a new energy automobile and a preparation method thereof, and belongs to the technical field of cable materials. The cable material is prepared from the following raw materials in parts by weight: 65 to 80 parts of ethylene acetic ether, 50 to 60 parts of polyethylene, 5 to 10 parts of polyethylene wax, 15 to 25 parts of maleic anhydride grafted polyethylene, 50 to 100 parts of porcelainized powder, 40 to 45 parts of ammonium polyphosphate, 30 to 60 parts of magnesium hydroxide and 0.2 to 0.5 part of antioxidant. The cable material prepared by the invention has excellent fireproof, low-smoke, halogen-free and flame-retardant properties and excellent porcelainizing performance, keeps a certain shape and strength in a combustion process, does not spread fire, and has an excellent fireproof function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and specifically relates to a porcelainizable fireproof, low-smoke, halogen-free polyolefin cable material for new energy vehicles and a preparation method thereof. Background Art

[0002] Compared with traditional fuel vehicles, new energy vehicles can save energy to a large extent. However, compared with traditional fuel vehicles, new energy vehicles have added many high-voltage accessories, such as power batteries, high-voltage distribution boxes, drive motors, motor controllers, etc., which increases the need for automotive cables. After a fire or explosion occurs in a new energy vehicle, the polymer base cable bundle can easily burn the cable insulation layer instantly, causing a short circuit and power outage. As the wire and cable materials for power or signal transmission in new energy vehicles, due to the special environment, they are more likely to cause combustion due to overheating, damage the normal power supply of the cable, cause the intelligent central control system to fail in the fire, and cause the car door to be unable to open, which seriously endangers the safety of people's lives and property.

[0003] Cable materials with traditional halogen flame retardants will release a large amount of toxic and corrosive smoke after burning. Therefore, new halogen-free and environmentally friendly flame retardants are gradually being developed and applied. However, flame retardants cannot completely prevent fires or reduce the damage caused by fires. They only delay the burning time and have a great impact on the performance of the materials. At present, magnesium oxide mineral insulated fireproof cables and mica tape wound fire-resistant cables are mostly used at home and abroad, but these two types of cables have obvious disadvantages. The outer sheath of magnesium oxide mineral cables is all copper, the raw material cost is high, it is difficult to use on a large scale, and it is difficult to lay and install; mica tape wound fire-resistant cables are prone to defects because they need to be wound in multiple layers, and they perform poorly in terms of fire resistance.

[0004] Therefore, it is necessary to provide a vitrified fire-proof, low-smoke, halogen-free polyolefin cable material for new energy vehicles. Summary of the invention

[0005] In view of the above problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a ceramic fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles, which has excellent fireproof, low-smoke, halogen-free flame retardant properties and excellent ceramic and fireproof properties. The second technical problem to be solved by the present invention is to provide a preparation method of a ceramic fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles, which is simple and convenient, and the prepared cable material has excellent flame retardant and fireproof properties, and is used to deal with the current problem of burning and spreading of cables in new energy vehicles.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A porcelainized fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles is prepared from the following raw materials in parts by weight: 65-80 parts of ethylene ethyl acetate, 50-60 parts of polyethylene, 5-10 parts of polyethylene wax, 15-25 parts of maleic anhydride grafted polyethylene, 50-100 parts of porcelain powder, 40-45 parts of ammonium polyphosphate, 30-60 parts of magnesium hydroxide and 0.2-0.5 parts of antioxidant.

[0008] Furthermore, it is made from the following raw materials in parts by weight: 65-70 parts of ethylene ethyl acetate, 55-60 parts of polyethylene, 6-8 parts of polyethylene wax, 20-22 parts of maleic anhydride grafted polyethylene, 60-80 parts of porcelain powder, 41-43 parts of ammonium polyphosphate, 30-55 parts of magnesium hydroxide and 0.2-0.4 parts of antioxidant.

[0009] Furthermore, the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder.

[0010] Furthermore, the mass ratio of the kaolin, mica powder, calcium carbonate and glass powder is 1-10:5-20:1-5:10-30.

[0011] Furthermore, the mass ratio of kaolin, mica powder, calcium carbonate and glass powder is 2~8:5~10:1~3:10~20.

[0012] Furthermore, the mass ratio of the kaolin, mica powder, calcium carbonate and glass powder is 5:6:3:13.

[0013] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0014] A method for preparing a porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles, the specific steps are as follows:

[0015] 1) Weigh the porcelain powder and ammonium polyphosphate, mix them, dry them, and discharge them for later use;

[0016] 2) mixing ethylene ethyl acetate, polyethylene, polyethylene wax, maleic anhydride grafted polyethylene, magnesium hydroxide, antioxidant and the mixture prepared in step 1) uniformly and performing banburying;

[0017] 3) The raw materials mixed in step 2) are extruded and granulated on a twin-screw extruder at a barrel temperature range of 110-150° C., and the cable material is obtained after drying.

[0018] Furthermore, in step 1), the drying temperature is 50-60°C.

[0019] Furthermore, in step 2), the mixing temperature is 150-160°C.

[0020] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0021] (1) The cable material prepared by the present invention has excellent fire-proof, low-smoke, halogen-free flame retardant properties and excellent vitrification properties. It maintains a certain shape and strength during the combustion process and will not spread the fire, thus having excellent fire-proof function.

[0022] (2) The present invention controls the porcelain fireproof performance of the cable material by designing and selecting the component types of the porcelain powder and adjusting the proportion of the porcelain powder. The prepared cable material has excellent flame retardant and fireproof properties. When the new energy vehicle is in a fire, it will not explode instantly and is easy to sinter into porcelain, thereby protecting the power supply safety of the intelligent central control system of the new energy vehicle.

[0023] (3) The cable material prepared by the present invention has excellent flame retardant and fireproof properties, and also has multiple functions of heat insulation, smoke suppression, halogen-free and fireproof, and will not cause dripping.

[0024] (4) The preparation method of the present invention is simple and convenient, easy to operate, and easy to be mass-produced industrially. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with specific embodiments.

[0026] Example 1

[0027] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0028] (1) Weigh 50 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 1:5:2:12;

[0029] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0030] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0031] Example 2

[0032] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0033] (1) Weigh 60 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 1:5:2:12;

[0034] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0035] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0036] Example 3

[0037] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0038] (1) Weigh 70 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 1:5:2:12;

[0039] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0040] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0041] Example 4

[0042] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0043] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 1:5:2:12;

[0044] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0045] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0046] Example 5

[0047] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0048] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 2:6:3:13;

[0049] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0050] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0051] Example 6

[0052] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0053] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 5:6:3:13;

[0054] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0055] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0056] Example 7

[0057] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0058] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 7:6:3:13;

[0059] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0060] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0061] Example 8

[0062] The preparation steps of vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles are as follows:

[0063] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder in a mass ratio of 8:6:3:13;

[0064] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0065] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0066] Comparative Example 1

[0067] The preparation steps of cable materials for new energy vehicles are as follows:

[0068] (1) Weigh 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use;

[0069] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0070] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0071] Comparative Example 2

[0072] The preparation steps of cable materials for new energy vehicles are as follows:

[0073] (1) Weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is kaolin;

[0074] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0075] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0076] Comparative Example 3

[0077] The preparation steps of cable materials for new energy vehicles are as follows:

[0078] (1) Weigh 80 parts of ceramic powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the ceramic powder is mica powder;

[0079] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0080] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0081] Comparative Example 4

[0082] The preparation steps of cable materials for new energy vehicles are as follows:

[0083] (1) By weight, weigh 80 parts of ceramic powder and 40 parts of ammonium polyphosphate, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the ceramic powder is calcium carbonate;

[0084] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0085] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0086] Comparative Example 5

[0087] The preparation steps of cable materials for new energy vehicles are as follows:

[0088] (1) By weight, weigh 80 parts of porcelain powder and 40 parts of ammonium polyphosphate, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the porcelain powder is white carbon black;

[0089] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0090] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0091] Comparative Example 6

[0092] The preparation steps of cable materials for new energy vehicles are as follows:

[0093] (1) Weigh 80 parts of ceramic powder and 40 parts of ammonium polyphosphate by weight, mix them, dry them at 60°C for 5 minutes, and discharge them for later use; wherein the ceramic powder is glass powder;

[0094] (2) Weigh 70 parts by weight of ethylene ethyl acetate, 60 parts of polyethylene, 5 parts of polyethylene wax, 15 parts of maleic anhydride grafted polyethylene, 30 parts of magnesium hydroxide, 0.3 parts of 2,6-di-tert-butyl-4-methylphenol and the mixture prepared in step (1), mix them evenly, and put them into an internal mixer for mixing at a temperature of 160° C. for 15 minutes;

[0095] (3) The raw materials mixed in step (2) are extruded and granulated on a twin-screw extruder at a barrel temperature ranging from 110 to 150° C., and then dried to obtain the cable material.

[0096] The properties of the cable materials prepared in Examples 1 to 8 and Comparative Examples 1 to 6 were tested, and the results are shown in the following table.

[0097] Table 1 Mechanical properties test results

[0098]

[0099] It can be seen from the data in Table 1 that the porcelain-able fire-proof low-smoke halogen-free polyolefin cables of Examples 1-8 can meet the national standards, have excellent porcelain-ability, maintain a certain shape and strength during the combustion process, will not spread the fire, and have multiple functions of heat insulation, smoke suppression, halogen-free and fire prevention.

[0100] At 2.5mm 2 The copper core conductor is coated with the cable materials prepared in Examples 1 to 8 and Comparative Examples 1 to 6, and a line integrity fire resistance test is performed in accordance with the national standard GB / T19216.21-2003. The results are shown in Table 2 below.

[0101] Table 2 Fire resistance test results

[0102]

[0103] It can be seen from the data in Table 2 that, compared with the comparative example, the cable material prepared by the present invention has excellent fire-proof, low-smoke, halogen-free flame retardant properties, and has excellent vitrification properties, maintains a certain shape and strength during the combustion process, will not spread the fire, and has excellent fireproof function.

[0104] The ablation results of Examples 1 to 8 and Comparative Examples 1 to 6 are shown in Table 3 below.

[0105] Table 3 Ablation results of samples of Examples 1 to 8 and Comparative Examples 1 to 5

[0106]

[0107] It can be seen from the data in Table 3 that after ablation at 700°C and 900°C, the cables of Examples 1-8 remain uniform and intact, and no molten droplets occur, thereby protecting the power supply safety of the intelligent central control system of new energy vehicles.

Claims

1. A vitrified fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles, characterized in that: The invention is prepared from the following raw materials in parts by weight: 65-80 parts of ethylene ethyl acetate, 50-60 parts of polyethylene, 5-10 parts of polyethylene wax, 15-25 parts of maleic anhydride grafted polyethylene, 50-100 parts of porcelain powder, 40-45 parts of ammonium polyphosphate, 30-60 parts of magnesium hydroxide and 0.2-0.5 parts of antioxidant.

2. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 65-70 parts of ethylene ethyl acetate, 55-60 parts of polyethylene, 6-8 parts of polyethylene wax, 20-22 parts of maleic anhydride grafted polyethylene, 60-80 parts of porcelain powder, 41-43 parts of ammonium polyphosphate, 30-55 parts of magnesium hydroxide and 0.2-0.4 parts of antioxidant.

3. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 1, characterized in that: The porcelain powder is a mixture of kaolin, mica powder, calcium carbonate and glass powder.

4. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 3, characterized in that: The mass ratio of the kaolin, mica powder, calcium carbonate and glass powder is 1-10:5-20:1-5:10-30.

5. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 4, characterized in that: The mass ratio of the kaolin, mica powder, calcium carbonate and glass powder is 2-8:5-10:1-3:10-20.

6. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 5, characterized in that: The mass ratio of the kaolin, mica powder, calcium carbonate and glass powder is 5:6:3:

13.

7. The porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 1, characterized in that: The antioxidant is 2,6-di-tert-butyl-4-methylphenol.

8. A method for preparing a porcelainizable fireproof, low-smoke, halogen-free polyolefin cable material for new energy vehicles, characterized in that: The specific steps are as follows: 1) Weigh the porcelain powder and ammonium polyphosphate, mix them, dry them, and discharge them for later use; 2) mixing ethylene ethyl acetate, polyethylene, polyethylene wax, maleic anhydride grafted polyethylene, magnesium hydroxide, an antioxidant and the mixture prepared in step 1) uniformly and kneading; 3) The raw materials mixed in step 2) are hot pressed, and after the hot pressing is completed, they are cold pressed to obtain cable materials.

9. The method for preparing the porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 8, characterized in that: In step 1), the drying temperature is 50-60°C.

10. The method for preparing the porcelainizable fireproof low-smoke halogen-free polyolefin cable material for new energy vehicles according to claim 8, characterized in that: In step 2), the mixing temperature is 80-90°C.